Penerapan Media Scrabble dalam Meningkatkan Keaktifan dan Kognitif Siswa pada Pembelajaran Ilmu Pengetahuan Sosial Siswa Kelas VII MTs Darul Hikmah Tulungagung - Nilna Afifatul Alfiyah; Nur Isroatul Khusna (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2025)
This research is motivated by the low learning outcomes and activeness of class VII F students of MTs Darul Hikmah Tulungagung in Social Studies (IPS) lessons due to the use of monotonous lecture methods. The purpose of this study is to improve students' activeness and cognitive abilities through the application of board-based scrabble media. This research is a Classroom Action Research (CAR) which was carried out in two cycles with four stages: planning, implementation, observation, and reflection. The research subjects were 27 students, with data collection techniques through tests, observation, and documentation, and data analysis using average scores. Student activeness was observed based on learning activeness indicators, while cognitive abilities were measured through pre-tests and post-tests based on Bloom's taxonomy. The results of the study showed an increase in student activeness from 62% in cycle I to 87% in cycle II, as well as an increase in the average cognitive ability from 18.51% to 77.77%. These findings indicate that scrabble media is effective in improving students' activeness and cognitive abilities in IPS learning. The implication is that game-based learning media can be widely applied to non-language materials to create more interactive and meaningful learning.